Utilizing Electromagnetic Radiation in Remote Sensing for Vegetation Health Analysis Using NDVI Approach with Sentinel-2 Imagery - Pamuji, Rizky; Mahardika, Andi Ichsan; Wiranda, Nuruddin; Saputra, Novan Alkaf Bahraini; Adini, Muhammad Hifdzi; Pramatasari, Delsika (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2023)
The process of utilizing electromagnetic radiation from the radiometric values (Near-Infrared/NIR) and RED in the Normalized Difference Vegetation Index (NDVI) on Sentinel-2 imagery involves measuring light reflection at specific wavelengths reflected by vegetation. NDVI is computed by taking the difference between NIR and RED reflectance, then dividing it by their sum. In-depth analysis of electromagnetic wave interaction and plant spectral characteristics, such as NIR light reflection in healthy leaves, enables mapping vegetation health levels. The research aims to process image data and create a model visualizing vegetation health in the Sentinel-2 research area. Across the total area of 601,971,281.26 m2, 30.37% is healthy vegetation, 12.52% is moderate, and 53.33% is low or unhealthy. The least healthy area has an NDVI of -0.2006, while the healthiest area has a value of 0.6043.